Finance and Misallocation: Evidence from Plant-Level Data - Midrigan, Virgiliu; Xu, Daniel Yi (American Economic Review, 2014)
We use producer-level data to evaluate the role of financial frictions in determining total factor productivity (TFP). We study a model of establishment dynamics in which financial frictions reduce TFP through two channels. First, finance frictions distort entry and technology adoption decisions. Second, finance frictions generate dispersion in the returns to capital across existing producers and thus productivity losses from misallocation. Parameterizations of our model consistent with the data imply fairly small losses from misallocation, but potentially sizable losses from inefficiently low levels of entry and technology adoption. (JEL E32, E44, F41, G32, L60, O33, O47)